2011
DOI: 10.1159/000332213
|View full text |Cite
|
Sign up to set email alerts
|

The Intriguing Relationship of <i>Helicobacter pylori</i> Infection and Acid Secretion in Peptic Ulcer Disease and Gastric Cancer

Abstract: Helicobacter pylori infection induces chronic inflammation of the gastric mucosa and thus profoundly affects gastric physiology. In the acute phase of infection, gastric acid secretion is transiently impaired. The morphological damage of the gastric mucosa, changes in gastric hormone release, and disruption of neural pathways all contribute to influence gastric acid secretion in a distinct manner. Changes in gastric acid secretion, whether impaired or increased, are intimately related with the topographic phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 68 publications
1
47
0
6
Order By: Relevance
“…Este fenó-meno pudiese vincularse con lo reportado por Tsukui et al 24 , quienes sugirieron que, en pacientes con dispepsia, la presencia de úlcera duodenal disminuye el riesgo de desarrollar gastritis atrófica y metaplasia intestinal en el cuerpo gás-trico. La presencia de úlcera duodenal se asocia a pocos cambios atróficos, gastritis predominantemente antral y bajo riesgo de desarrollar cáncer gástrico 25 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Este fenó-meno pudiese vincularse con lo reportado por Tsukui et al 24 , quienes sugirieron que, en pacientes con dispepsia, la presencia de úlcera duodenal disminuye el riesgo de desarrollar gastritis atrófica y metaplasia intestinal en el cuerpo gás-trico. La presencia de úlcera duodenal se asocia a pocos cambios atróficos, gastritis predominantemente antral y bajo riesgo de desarrollar cáncer gástrico 25 .…”
Section: Discussionunclassified
“…Se ha reportado que las poblaciones localizadas a nivel del mar consumen mayores cantidades de pescado, vegetales y frutas frescas, y presentan mayores tasas de parasitosis intestinal por helmintos 6,36 . Esta última circunstancia genera una respuesta inmunitaria predominantemente tipo Th2, que se vincula con la evasión de la gastritis atrófica y menor efecto antisecretor de algunas citocinas proinflamatorias 6,25,36 .…”
Section: Discussionunclassified
“…21,22 Firstly, the infection of the stomach by H. pylori induces inflammation of the gastric mucosa (gastritis) and is estimated that occur in the most patients infected by H. pylori. 23 H. pylori infection may be associated with decreased or increased gastric acid secretion, depending on the distribuition and severity of gastritis. 4 The interplay of gastritis and acid secretion are key determinants in disease outcomes such as peptic ulcer and/or gastric cancer.…”
Section: Helicobacter Pylori Infection: From Gastric Inflammation Tomentioning
confidence: 99%
“…4 The interplay of gastritis and acid secretion are key determinants in disease outcomes such as peptic ulcer and/or gastric cancer. 23 Ulceration corresponds to the loss of mucosal integrity as the result of disequilibrium between defensive mucosa-protective factors (mucus bicarbonate layer and phospholipid surfactant layer) and aggressive injurious factors (strong acid and high proteolytic activity in gastric secretions). When ulcers develop in the acid-peptic environment of the gastroduodenum, they are called peptic ulcer disease.…”
Section: Helicobacter Pylori Infection: From Gastric Inflammation Tomentioning
confidence: 99%
“…(39) This could be explained by the relation between the location of gastritis and the amount of acid secretion; corpus-predominant gastritis is accompanied by hypochlorhydria and results in the highest risk for GC, whereas antrum-predominant gastritis is associated with hyperchlorhydria and predisposes to DU disease. (40,41) As PSCA is not expressed in the duodenum, its function in the stomach might affect DU development, possibly through such effects as those related to acid secretion, location and extent of HP infection or gastritis. It was also reported that the T allele was especially associated with noncardia GC in Chinese and Caucasian patients but with cardia GC in Korean patients.…”
Section: à6mentioning
confidence: 99%